Desmoid-type fibromatosis of the breast in a male patient following cosmetic surgery: a rare case report - Correa Sandoval, Diana Carolina; Gonzalez Reyes, Javier; Guajardo Nieto, Diego Alberto; Guzman Murguia, Jose Luis (Frontiers in Oncology, 2024)
BackgroundDesmoid-type fibromatosis of the breast is a rare, benign, but locally aggressive tumor that typically affects women. Its presentation in male patients is exceedingly rare, and even more so following a cosmetic procedure such as liposuction. This case report describes a unique presentation of breast fibromatosis in a male patient, who developed the condition after undergoing liposuction for cosmetic purposes to define the pectoral area. The case highlights the diagnostic challenges it poses due to its malignancy-like appearance on imaging.Materials and methodsA 28-year-old male patient presented with a right palpable mass in the breast following a liposuction procedure aimed at enhancing pectoral definition. Imaging studies, including ultrasound and MRI, raised suspicion of a malignancy. However, histopathological analysis from a core needle biopsy revealed fibromatosis. The patient underwent surgical excision of the tumor, and histological evaluation confirmed the diagnosis of benign desmoid-type breast fibromatosis.ResultsHistopathological examination revealed benign fibromatosis with no evidence of malignancy. The tumor was completely excised with clear margins, and the patient has had no signs of recurrence during the follow-up period.ConclusionsThis case highlights the rare occurrence of breast fibromatosis in a male patient following liposuction for cosmetic purposes. Given its ability to mimic malignancy on imaging, early diagnosis and complete surgical excision are essential for effective management and to prevent recurrence.